2009
DOI: 10.1097/dbp.0b013e3181b0f035
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Early Childhood Development in Primary Health Care: Experience from a Middle-Income Country

Abstract: In Turkey and potentially other countries with similar health systems, short-term inservice training on child development can improve primary health providers' knowledge, perceived competence and skills related to child development. To decrease the disparities between high- and low- and middle-income countries in addressing child development, significant barriers within health systems need to be identified and addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
1
19
0
5
Order By: Relevance
“…22,23 In an improvement in the knowledge and practices of these professionals in an immediate assessment and in one conducted a year after the training. 25 Other studies have also demonstrated the effectiveness of child development training processes that are aimed at medical students and primary healthcare professionals, in institutional programs that ensure not only health promotion and disability prevention but also care for children who have been identified as presenting a problem in their development. 26,27 Parents' opinions regarding their children's development have been recognized by many researchers as having high sensitivity and specificity for detecting possible disorders.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In an improvement in the knowledge and practices of these professionals in an immediate assessment and in one conducted a year after the training. 25 Other studies have also demonstrated the effectiveness of child development training processes that are aimed at medical students and primary healthcare professionals, in institutional programs that ensure not only health promotion and disability prevention but also care for children who have been identified as presenting a problem in their development. 26,27 Parents' opinions regarding their children's development have been recognized by many researchers as having high sensitivity and specificity for detecting possible disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that there are multiple factors that influence the acceptance and practice of early detection and intervention, although data are limited. These include physician attitudes, awareness, or interest; 43 insufficient training; 44 doubt about the value of early detection or non‐acceptance of early treatment; 45 uncertainty about how or where to refer; 46 time limitations of the clinic visit and inadequate reimbursement; 47 and cost factors 48 . In some cases practitioners might be legitimately concerned about unnecessarily alerting a family and would prefer to wait until the problem is too obvious to ignore 49 .…”
Section: Current Practice Of Early Detection and Interventionmentioning
confidence: 99%
“…, is a comprehensive package that comprises three components: monitoring, supporting early childhood development and early intervention . The theoretical conceptualisation of the GMCD, research on its standardisation, reliability, validity and applicability in Turkey and its international use has previously been reported . The GMCD is based on a family‐centred, strengths‐based philosophy and it differs from screening tools in a number of ways.…”
Section: Introductionmentioning
confidence: 99%